Step-by-step bleeding management in cesarean section - Winata, I Gede Sastra; Wibawa, I Gusti Ngurah Agung Satria (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2023)
Cesarean sections have recently increased dramatically worldwide in the last 50 years. Unfortunately, the post-cesarean section maternal morbidity rate is reported to be relatively high, which is as high as 36%. Some of the most common complications of cesarean section are fever (25%), bleeding (4%), hematoma (4%), and urinary tract infection (3%). Among these complications, obstetric hemorrhage is one of the most common causes of maternal death worldwide. Excessive hemorrhage associated with a cesarean section is defined as blood loss above 1000 ml is frequently underestimated, but is documented as occurring in more than 5–10% of cesarean sections. In most cases, this can be treated with conservative treatment such as vaginal packing and administration of uterotonic drugs. However, some persistent bleeding cases require specific treatment and techniques during the operation. Therefore it is essential to understand the steps and procedures for handling bleeding during cesarean section to reduce maternal mortality. This article review aims to summarize some techniques that can be used to control bleeding during cesarean section.